Atomically Dispersed Transition Metals on Carbon Nanotubes with UltraHigh Loading for Selective Electrochemical Carbon Dioxide Reduction - Cheng, Yi; Zhao, S.; Johannessen, B.; Veder, Jean-Pierre; Saunders, M.; Rowles, Matthew; Cheng, M.; Liu, C.; Chisholm, M.; De Marco, Roland; Cheng, H.; Yang, S.; et al. (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Single-atom catalysts (SACs) are the smallest entities for catalytic reactions with projected high atomic efficiency, superior activity, and selectivity; however, practical applications of SACs suffer from a very low metal loading of 1-2 wt%. Here, a class of SACs based on atomically dispersed transition metals on nitrogen-doped carbon nanotubes (MSA-N-CNTs, where M = Ni, Co, NiCo, CoFe, and NiPt) is synthesized with an extraordinarily high metal loading, e.g., 20 wt% in the case of NiSA-N-CNTs, using a new multistep pyrolysis process. Among these materials, NiSA-N-CNTs show an excellent selectivity and activity for the electrochemical reduction of CO 2 to CO, achieving a turnover frequency (TOF) of 11.7 s -1 at -0.55 V (vs reversible hydrogen electrode (RHE)), two orders of magnitude higher than Ni nanoparticles supported on CNTs.